Studies on in silico and in vitro Anticancer Activity of Selected Plant Extract Phytocompounds against HeLa and HCT116 Cell Lines - Subbulakshmi, Essakki; Kumaresan, Sudalaiyanminudi; Palanisamy, Pandaram (International Journal of Pharmaceutical Investigation, 2025)
Background This study explores the phytochemical composition, molecular interactions and cytotoxic potential of ethanolic extracts from four medicinal plants-Solanum virginianum, Hibiscus rosa-sinensis, Piper betle and Eclipta alba-against cervical (HeLa) and colon (HCT116) cancer cell lines. Materials and Methods Qualitative phytochemical analysis was performed to identify bioactive compounds, including proteins, phenols, flavonoids and terpenoids. GC-MS analysis provided insights into key phytoconstituents such as fatty acids, steroids and diterpenoids. Molecular docking evaluated the binding affinities of major compounds like stigmasterol and skimmien against cancer targets, comparing their energies to the reference drug camptothecin. Cytotoxic activity was assessed using IC50 assays. Conclusion Eclipta alba emerged as the most potent extract, showing the lowest IC50 values (30 µg/mL for HeLa and 24 µg/mL for HCT116). Molecular docking revealed strong binding affinities for certain phytoconstituents, suggesting potential mechanisms of action. The phytochemical profile highlighted diverse bioactive compounds contributing to the observed cytotoxic effects. This study identifies Eclipta alba as a promising candidate for cancer therapy, supported by its significant cytotoxicity and strong molecular interactions. The findings provide a foundation for further research into these plant extracts as complementary agents in cancer treatment.
Keywords: Anticancer activity; Eclipta alba; Hibiscus rosa sinensis; Molecular docking; Phytocompounds; Piper betle; Solanum virginianum.